Instilling Multicultural Values ​​in Each Religious Adherent as a Form of Tolerance in the School Community (Study of SMAN 3 Mataram) - Anggun Dwi Andriani; Baiq Fina Maulidiya; M Salman Hanapi; Ni Nyoman Purnamiasih; Nureka Agisna Safira; Hayatunnisa; Sawaludin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This research aims to find 1) Special activities that can strengthen attitudes of tolerance among school members, 2) Implementation of attitudes of tolerance between religious communities at SMAN 3 Mataram, 3) Challenges faced in managing religious diversity in the school environment, 4) results obtained from the education of tolerance between religious communities that has been implemented. This research uses a descriptive method with a qualitative approach based on the characteristics of a phenomenon or problem. Data was collected through observation, interviews and documentation methods carried out at the research location. The results of observations obtained at SMAN 3 Mataram show 1) teacher perceptions regarding religious diversity and tolerance between religious communities in the school environment 2) Student responses to multicultural values, 3) SMAN 3 Mataram facilitates various activities designed to accommodate religious diversity in the school environment . One of the main activities is Imtaq (Faith and Taqwa) 4) The main challenge is how to organize and manage this diversity so that it runs according to the flow and needs of each religious follower.